Combining ability, heterotic patterns and genetic diversity of extraearly yellow inbreds under contrasting environments - Badu-Apraku, Baffour; Oyekunle, M.; Fakorede, M.A.B.; Vroh Bi, Irie; Akinwale, R.; Aderounmu, R.O. (Springer, 2013)
Information on the combining ability, heterotic patterns and genetic diversity of maize (Zea mays L.) inbreds is crucial for the success of a hybrid program targeting the stress environments of West Africa (WA). Studies were conducted in 2011 at four locations in Nigeria to (i) determine the combining ability of 20 extra-early yellow inbred lines, (ii) classify the inbred lines into heterotic groups, and (iii) determine the genetic diversity among the lines. General combining ability (GCA) effects were greater than specific combining ability (SCA) effects across test environments suggesting that additive gene action was more important than the nonadditive in the set of inbred lines. The lines were classified into four heterotic groups based on SCA effects, and three groups based on heterotic groups’ specific and GCA, the GCA effects of multiple traits of inbred lines and molecular markers. TZEEI 79, TZEEI 67, and TZEEI 81 were the best inbred testers while TZEEI 95 9 TZEEI 79 was the best single-cross tester. TZEEI 88 9 TZEEI 66 and TZEEI 96 9 TZEEI 73 were identified as ideal hybrids for further testing, promotion for adoption and commercialization in WA.